2019
DOI: 10.1158/1078-0432.ccr-18-2804
|View full text |Cite
|
Sign up to set email alerts
|

C8orf76 Promotes Gastric Tumorigenicity and Metastasis by Directly Inducing lncRNA DUSP5P1 and Associates with Patient Outcomes

Abstract: Purpose: We identified for the first time that C8orf76 (chromosome 8 open reading frame 76) is preferentially amplified in gastric cancer. We elucidated its role and clinical significance in gastric carcinogenesis. Experimental Design: The clinical impact of C8orf76 was assessed in 592 patients with gastric cancer. The biological function of C8orf76 was studied in vitro, in vivo, and in gastric cancer patient-derived organoid models. C8orf76 downstream effector and pathways were identified by RNA sequencing, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Gastric cancer is the fifth most common malignancy with a third highest cancer associated death rate [12]. Recently, various studies have suggested that lncRNAs are closely related to the carcinogenesis and development of GC [13][14][15][16][17]. LncRNA TINCR could promote the metastatic ability of GC cells by regulating the stability of KLF2 [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the fifth most common malignancy with a third highest cancer associated death rate [12]. Recently, various studies have suggested that lncRNAs are closely related to the carcinogenesis and development of GC [13][14][15][16][17]. LncRNA TINCR could promote the metastatic ability of GC cells by regulating the stability of KLF2 [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies validated that LINC00460 is a PRDX1-initiated lncRNA in head and neck squamous cell carcinoma [20]. C8orf76 directly binds to lncRNA DUSP5P1 promoter and induces lncRNA expression in gastric cancer [21]. However, the transcription of LINC01123 in TNBC remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the veyear survival rate of patients with advanced GC is < 20% 20,21 . Increasing numbers of studies have found that lncRNAs can act as critical regulators in GC metastasis and tumor growth, potentially becoming promising targets for GC treatment [22][23][24] . LINC01235 is a large intergenic noncoding RNA that is located on human chromosome 9p23 and has three exons.…”
Section: Discussionmentioning
confidence: 99%